PENINGKATAN KOMPETENSI GURU DALAM MENDESAIN PEMBELAJARAN DARING PADA MASA PANDEMI COVID-19 MELALUI IHT (IN HOUSE TRAINING) DI SMP NEGERI 8 KUBU TAHUN PELAJARAN 2020/2021 - Wahyudi, Wahyudi (Universitas Tanjungpura, 2022)
This online learning process has many meanings, from positive to negative. When studying online, teachers need to be as prepared as possible and provide materials as creatively as possible. The online learning process is not easy, especially in middle school (SMP). Not only teachers and students are involved in this online learning process, but parents also need to be involved in this online learning process. Therefore, this study aims to investigate the effectiveness of IHT activities in empowering teachers in the design of online learning tools. Evaluation of increased teacher activity in attending IHT concludes based on the results of IHT implementation (in-house training) conducted at SMP Negeri 8 Kubu to improve teachers' ability to develop online learning implementation plans we can attach it. Activities from 20.8 in cycle 1 to 25 in cycle 2 (internal training). On the other hand, teachers' ability to create online learning implementation plans was also enhanced before IHT activities (internal training), but teachers' ability to create online learning implementation plans averaged only 57.95%. I didn't. The average success rate for Cycle 1 was 71.59%, but increased to 93.18% for Cycle 2. Therefore, IHT (In House Training) activities can improve teachers' ability to plan online learning practices at SMP Negeri 8 Kubu